2017
DOI: 10.3389/fgene.2017.00157
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Receptor and Non-receptor Mediated Chemical Modes of Action in Rat Livers Converges through a Dysregulated Gene Expression Network at Tumor Suppressor Tp53

Abstract: Chemicals, toxicants, and environmental stressors mediate their biologic effect through specific modes of action (MOAs). These encompass key molecular events that lead to changes in the expression of genes within regulatory pathways. Elucidating shared biologic processes and overlapping gene networks will help to better understand the toxicologic effects on biological systems. In this study we used a weighted network analysis of gene expression data from the livers of male Sprague-Dawley rats exposed to chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Still, we found that clustering based on 1,510 DEGREEs resulted in interleaved MOA groups, except for PPARA (Figure 4A ). This kind of transcriptional cross-talk among 1,510 DEGREEs has been previously reported for this same dataset, suggesting that downstream pathways elicited by different chemical agents under the same MOA classification can converge to the same regulatory hubs through different molecular cascades and lead to distinctive transcriptional effects; conversely, chemical agents classified under different MOA can exhibit similar transcriptional signatures just as well (Funderburk et al, 2017 ).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Still, we found that clustering based on 1,510 DEGREEs resulted in interleaved MOA groups, except for PPARA (Figure 4A ). This kind of transcriptional cross-talk among 1,510 DEGREEs has been previously reported for this same dataset, suggesting that downstream pathways elicited by different chemical agents under the same MOA classification can converge to the same regulatory hubs through different molecular cascades and lead to distinctive transcriptional effects; conversely, chemical agents classified under different MOA can exhibit similar transcriptional signatures just as well (Funderburk et al, 2017 ).…”
Section: Resultssupporting
confidence: 76%
“…With the LSTNR method, the improvements in homoscedasticity by resolution scaling of Log2FC differences allow experimental designs with multiple groups to be tested by standard ordinary ANOVA techniques. Furthermore, DEGs detected by the LSTNR method capture the same transcriptional signatures at different tiers of statistical stringency with high accuracy; we found the performance of the LSTNR method was so robust that it required less genes than previously reported to discriminate breast cancer phenotypes and hepatotoxic MOAs using the same experimental datasets (Perou et al, 2000 ; Cancer Genome Atlas, 2012 ; Gong et al, 2014 ; Wang et al, 2014 ; Li and Bushel, 2016 ; Funderburk et al, 2017 ). As an added benefit, the LSTNR method can produce noise benchmarking estimates to validate RNAseq experiments against by benchtop techniques, regardless of statistical significance or sample replication levels.…”
Section: Discussionmentioning
confidence: 60%
“…It is involved in DNA damage repair, can regulate energy metabolism and also inhibits tumor angiogenesis to suppress the development and progression of cancer. 23 26 Moreover, abnormalities in the TP53 signaling pathway were found in the more malignant tumors. It reported that the upregulation of TP53 activated the caspase-9 death pathway.…”
Section: Discussionmentioning
confidence: 99%
“…To reveal the molecular mechanisms underlying in the retinal effects CDDP in diabetic rats, we performed a genome-wide expression profiling analysis on total RNA isolated from the retinas of the HCDDP group and the diabetic group ( n = 3 in each group) ( Hargadon, 2015 ; Funderburk et al, 2017 ; Gambara et al, 2017 ; Li et al, 2017 ). We found that 262 genes were differentially expressed in the retinas of HCDDP-treated rats (fold change >1.5, P < 0.05).…”
Section: Resultsmentioning
confidence: 99%